A flow cytometric approach to study the mechanism of gene delivery to cells by gemini-lipid nanoparticles: an implication for cell membrane nanoporation. Issue 1 (December 2015) - Gharagozloo, Marjan; Rafiee, Amirreza; Chen, Ding; Foldvari, Marianna
Abstract Background Gemini-lipid nanoparticles have been received major attention recently as non-viral delivery systems due to their successful non-invasive gene delivery through tough barriers such as eye and skin. The aim of this study was to evaluate non-viral gene delivery by a series of dicationic gemini surfactant-phospholipid nanoparticles (GL-NPs) and to explore their mechanism of interaction with cellular membranes of murine PAM212 epidermal keratinocytes. Methods NPs containing pCMV-tdTomato plasmid encoding red fluorescent protein (RFP) were prepared using 12 different gemini surfactants (m-s-m, with m = 12, 16 and 18C alkyl tail and s = 3 and 7C polymethylene spacer group and 7C substituted spacers with 7NH and 7NCH3) and dioleoylphosphatidylethanolamine helper lipid. RFP gene expression and cell viability status were evaluated using flow cytometry. MitoTracker Deep Red mitochondrial stain and the cell impermeable Sytox red nuclear stain were used as indicators of cell viability and cell membrane integrity, respectively. Results No significant viability loss was detected in cells transfected with 18-3-18, 18-7-18, 18-7NH-18, and 18-7NCH3-18 NPs, whereas a significant reduction of viability was detected in cells treated with 12-3-12, 12-7-12, 12-7NH-12, 16-7NH-16, or 16-7NCH3-16 GL-NPs. Compared to Lipofectamine Plus, 18-3-18 GL-NPs showed higher transfection efficiency and comparable viability profile by evaluation using MitoTracker Deep Red in PAM212 cells. Flow cytometric analysis of PAM212 cells stained with Sytox red revealed two cell populations with low and high fluorescent intensity, representing cells with partially-porated and highly-porated membranes, respectively. Additional combined staining with MitoTracker and ethidium homodimer showed that that 18-3-18 GL-NPs disturbed cell membrane integrity, while cells were still alive and had mitochondrial activity. Conclusion Taken together, this study demonstrated that 18-3-18 GL-NPs have higher transfection efficiency and comparable viability profile to the commercial Lipofectamine Plus, and the interaction of 18-3-18 GL-NPs with PAM212 cell membranes involves a permeability increase, possibly through the formation of nanoscale pores, which could explain efficient gene delivery. This novel nanoconstruct appears to be a promising delivery system for further skin gene therapy studies in vivo.